Analysis of the Use of Excessive Graphic Design Elements on 77Th Independence Day Posters - Persada, S I P; Najibulloh, M (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Independence posters are posters that are often present when commemorating the Independence of the Indonesian Nation which are made by institutions, agencies or even individuals every year including for the 77th anniversary. The poster makers try to raise awareness about the importance of remembering the services of the heroes who fought for the independence of the Indonesian nation, the poster makers often use elements of independence in each of their posters. This study aims to identify and find out the use of redundant elements on the 77th Republic of Indonesia Independence Day Commemoration Posters which researchers often encounter in society on Independence Day. This study uses qualitative research methods to describe in detail which elements are redundant in the Posters commemorating the 77th Independence Day of the Republic of Indonesia by taking 1 sample poster from various government agencies. In the study it was concluded that the use of elements on the 77th Independence Day Commemoration Poster proved to be excessive with the repetition of elements that resembled the Indonesian Flag, Maps, Figures such as Soekano, Bung Tomo and even other Heroes, there were also found other elements such as ribbons -ribbons, people clenching their arms, broken chains and people raising flags. The researcher also concluded that the repetition of elements like the one above is to give a lively or lively impression on the poster, but it is not uncommon for repetition to make the poster difficult to read.